ESSAY ON THE COMPLEXITY OF PUBLIC SERVICE DELIVERY - Marques Pereira, Sandra Patrícia (2022)
Providing services to society is a challenging process for local governments, and it is a process that carries several risks. Government decisions will dictate the success or failure of a service delivered to citizens. These decisions are influenced by transaction costs (economic and political) and the costs of producing the service. By weighing both, governments decide which governance mechanism they will use to deliver the service. This essay aims to deepen the different topics that explain the complexity of service provision, delving deeper into the framework of transaction costs (economic and political), the models of production of public goods and services and the characteristics of services.